(untitled) (Journal of the College of Languages (JCL), 2024)
Pablo Neruda’s artistic distinctiveness can be considered in two ideas or attitudes of romanticism. First, the imagination, which is the result of conduct and spirituality, and second, the individualism, which is a collection of mysterious mysteries from the texts of individuality based on philosophical sonnets. His collection of poems points out the ethereality and indescribability of life, employing the reality of life at the level of human perception in a symbolic language. In other words, Pablo Neruda recreates the meanings in poetry through the three ideas of reduction, interpretation, and analysis. "What is the essential connection between individualism and the symbolic language of Pablo Neruda’s imagination and What are the reasons for this tendency to express symbolically in his poems?" are the main questions in this study. There is a dialectical relationship between these two components and the study of the dialectical relations between phenomena and the concepts of philosophical and historical origin has a long history. The dialectic of relationship detection is based on internal contradictions that arise with the philosophy of Socrates and Plato and conclude in Hegel’s thought. In Pablo Neruda’s poetry, the element of imagination moves from the social context, but eventually becomes something that has an individualistic character. Received on 3/5/2023 Accepted on 20/8/2023 Published on 2/1/2024